Best Answer

4n - 2n = 4 .

Before we continue with the solution to this problem,

it will help us to remember that

4 cows - 2 cows = 2 cows

4 beers - 2 beers = 2 beers

4 books - 2 books = 2 books

4 dollars - 2 dollars = 2 dollars.

Similarly, on the left side of the equation, 4n-2n = 2n.

So now the equation actually says

2n = 4

Divide each side by 2:

n = 2

Q: What 4n minus 2n equals 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Move the 2n over the equals sign. Become 4n (as 6n-2n= 4n) and then if 4n=16 then n=4.

4n - 7n = 21(4-7) n =21-3n = 21divide both sides by -3n = -7

I am assuming that 2n is an algebraic expression, and n is limited to positive integer values. The first 4 multiples of 2n are 0 (2n*0), 2n (2n*1), 4n (2n*2), and 6n (2n*3). If you are looking for non-0 multiples, you would also include 8n (2n*4).

4n+13=1 -13 -134n=-12/4 /4n=-3

4n + 24 = 484n + 24 - 24 = 48 - 244n + 24 - 24 = 48 - 244n = 48 - 244n = 244n/4 = 24/44n/4 = 24/4n = 24/4n = 6

Related questions

Move the 2n over the equals sign. Become 4n (as 6n-2n= 4n) and then if 4n=16 then n=4.

If you mean: 4n-2n = 4 then 2n = 4 and n = 2

6n -3=2n+9 6n-2n=9+3 4n=12 n=12/4 n=3

Suppose the number is N. Then 2N - 4 = 47 2N = 51 N = 25.5

4n - 7n = 21(4-7) n =21-3n = 21divide both sides by -3n = -7

First we must collect and simplify 'like terms' 2n-6n-36. 2n-6n = -4n Therefore, -4n-36 Take out the greatest common factor. -4 (n+9) Ans = -4 (n+9)

n - 16 = 2n + 12 + 3nCombine the 'n' terms on the right side:n - 16 = 5n + 12Subtract 'n' from each side:-16 = 4n + 12Subtract 12 from each side:-28 = 4nDivide each side by 4:-7 = n

2n-9=-4

4n = 48 4n/4 = 48/4 (Divide by 4 on both sides and then cancel) n = 12

FOIL deals with polynumerals in math. An example is a difference of squares as in (2n - 2)2 or (2n + 2)(2n - 2) =F stand for first--2n X 2n = 4n2O stands for outside-- 2n X -2 = -4nI stands for inside-- -2 X 2n = 4nL stands for last--2 X -2 = -4In the end you get:4n2 - 4n + 4n - 4 = 4n2 - 4Can you see how everything is squared and the two numbers are being subtracted?

4n + 3 = 15 4n +3 - 3 = 15 - 3 4n = 12 4n/4 = 12/4 n = 3

I am assuming that 2n is an algebraic expression, and n is limited to positive integer values. The first 4 multiples of 2n are 0 (2n*0), 2n (2n*1), 4n (2n*2), and 6n (2n*3). If you are looking for non-0 multiples, you would also include 8n (2n*4).